Synergism of Phage фPT1b and Antibiotics for Reducing Infection of Escherichia coli - Erlia Narulita; Gerda Permata Aji; Bevo Wahono; Siti Murdiyah; Ria Yulian (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2020)
Foodborne disease caused by Escherichia coli contamination is increasing every year. It also followed by elevating of drug-resistance of E. coli. Bacteriophage can be an alternative for therapy infection. This study aimed to determine synergism effect of bacteriophage ϕPT1b which has a high rate virulence to E. coli and phage-antibiotics (tetracycline and amoxicillin) synergy. The indigenous bacteria isolates were KR, MJ, KP, PT, PR. Five bacteriophages used namely ϕKR1b, ϕKR2, ϕPT1a, ϕPT1b, and ϕMJ1b. Virulence test was used to determine the ability of each phage in reducing E. coli. Treatment to examine synergism of phage ϕPT1b and antibiotics were P1: amoxicillin, P2: ϕPT1b, P3: ϕPT1b + Amx = 1:1, P4 : ϕPT1b + Amx = 2:1, P5: ϕPT1b + Amx = 1:2, P6 : tetracycline, P2: ϕPT1b, P7: ϕPT1b + Tet = 1:1, P8 : ϕPT1b + Tet = 2:1, and P9: ϕPT1b + Tet = 1:2. The virulence test showed that isolate ϕPT1a with 106 CFU/ml had the highest ability in reducing E. coli. While, the result of synergism test indicated that the synergism of bacteriophage and antibiotics differ significantly (P ≤ 0.05). The best ratios of synergism were 1:1 (ϕPT1b+tetracycline) and 2:1 (ϕPT1b+amoxicilline). In summarize, phage-antibiotic synergy (ϕPT1b with tetracycline/amoxicilline) can reduce the level of antibiotic resistance in isolated E. coli.